A Solution for Automatic Task Allocation in Software Development Teams based on Truck Factor and Implemented on GitHub and Trello - Oliveira, Dirlândia; Segundo, Caetano; Gonçalves, Enyo; Oliveira, Marcos de (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2026: Anais do XXII Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2026.248701, 2026)
Context: Software development involves several steps and activities. One of these activities is task allocation. This activity is related to project management and is decisive for the success or failure of the project since it involves risks related to time and, consequently, costs. Practical Problem: Inefficient task allocation, combined with team member rotation and knowledge concentration among a few members, can negatively impact deadlines, costs, and even lead to project discontinuation. Proposed Solution: All knowledge related to the project must be distributed equally among all team members to mitigate the negative impacts of possible departures of team members. This work proposes a web solution for task allocation that considers the knowledge level of the team members on the project repository. IS Theory: The approach builds on theories of project management, knowledge distribution, and collaborative software development, emphasizing metrics for team knowledge assessment. Research Method: A web application implementing the proposed approach was developed and evaluated in the context of software development teams. Summary of Results: The solution enables balanced knowledge distribution among team members, mitigating risks associated with departures and knowledge concentration, and improves task allocation efficiency. Contributions: The proposed approach provides a practical tool for software project management, enhancing knowledge management and reducing project risks, contributing to both the research and practice of Information Systems.